SARS‐CoV‐2 Omicron variant: Immune escape and vaccine development - Danyi Ao; Tianxia Lan; Xuemei He; Jian Liu; Li Chen; Daniel T. Baptista‐Hon; Kang Zhang; Xiawei Wei (MedComm, 2022)
Abstract New genetic variants of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) constantly emerge through unmitigated spread of the virus in the ongoing Coronavirus disease 2019 pandemic. Omicron (B.1.1.529), the latest variant of concern (VOC), has so far shown exceptional spread and infectivity and has established itself as the dominant variant in recent months. The SARS‐CoV‐2 spike glycoprotein is a key component for the recognition and binding to host cell angiotensin‐converting enzyme 2 receptors. The Omicron variant harbors a cluster of substitutions/deletions/insertions, and more than 30 mutations are located in spike. Some noticeable mutations, including K417N, T478K, N501Y, and P681H, are shared with the previous VOCs Alpha, Beta, Gamma, or Delta variants and have been proven to be associated with higher transmissibility, viral infectivity, and immune evasion potential. Studies have revealed that the Omicron variant is partially resistant to the neutralizing activity of therapeutic antibodies and convalescent sera, which poses significant challenges for the clinical effectiveness of the current vaccines and therapeutic antibodies. We provide a comprehensive analysis and summary of the epidemiology and immune escape mechanisms of the Omicron variant. We also suggest some therapeutic strategies against the Omicron variant. This review, therefore, aims to provide information for further research efforts to prevent and contain the impact of new VOCs during the ongoing pandemic.